Enhancing Competency-Based Learning Through Flipped Classroom Approach - Nsyengula, Stephen; Haule , J, Emmanuely; Mhagama, Willy; Wang'uba Okello, Joel (Journal of Classroom Action Research, 2024)
Implementation of competence-based education requires innovative teaching methodologies that actively engage learners and develop higher-order thinking skills. This study explored the effectiveness of flipped classrooms in enhancing competency-based learning through a qualitative case study of English instruction in secondary schools in the Mbeya region. Semi-structured interviews with English teachers revealed increased student preparation before class using pre-recorded video lessons and online resources under the flipped model. Focus group discussions with students reported improved understanding and retention through self-paced learning of content as homework. Document analysis of lesson plans and student assignments provided evidence of more profound analytical skills expected in competency-based curricula. Key findings highlight that the flipped classroom approach enabled learners to arrive at lessons equipped with introductory content knowledge. This allowed more class time for collaborative problem-solving activities, discussions, and applying learning to real-world scenarios. Students demonstrated enhanced communication, critical thinking, and self-directed learning abilities. The flipped model shows promise in promoting key competencies mandates, such as communication, collaboration, and digital literacy. Recommendations include scaling up the model through cluster-based teacher training programs and affordable technology support. Strategic integration into English and other subjects can transform learning outcomes to meet 21st-century competency demands. Keywords: Flipped classroom; Competency-Based Education; Innovative Teaching